Surveillance at Sea: Legal Aspects of Offshore Installation's Utilization - Afriansyah, Arie; Surtiwa, Salsabila Siliwangi (Universitas Negeri Semarang, 2020)
As the sea possesses rich variations of resources, it also imposes threats to the security and defense interests of a nation. Oil and gas exploration is one of the most important economic activities in the sea. In Indonesia, hundreds of offshore oil and gas platforms comprise thirty percent of the total oil and gas production. This signifies the importance of their establishment to the economy. However, their potentials do not stop there. As Indonesia is comprised of a very vast water area, the surveillance system still needs improvement. The article proposes to combine these interests into manifesting a simple surveillance system in offshore oil and gas platforms to improve defense and security systems, both for maritime routes in general and also the installations. The proposal prioritizes installations that are no longer operating, shifting their functions for other beneficial means. This is supported by the current law and regulations of the sea, both at the international and national levels. The international law of the sea implies that surveillance and data collection is allowed within the jurisdictional and territorial waters, whereas national levels allow functional shifting and defense system improvement in installations as long as it is coordinated with relevant ministries.